HAK DAN STATUS ANAK SYUBHAT DALAM PENIKAHAN - Fahmi Al Amruzi (Syariah: Jurnal Hukum dan Pemikiran, 2017)
Abstract: Allah has clearly established all good things that are lawful (halal) or forbidden (haram), and between them there is something called syubhat, where most people fall into it and they do not know whether it is halal or haram. If you do not know whether it is halal or haram will a thing, then will arise a phenomenon called as syubhat. A relationship that was made because there is an element of syubhat, whether that happens to a marriage, called syubhat and then to be fasakh, or occurs in watha' which is also called watha' syubhat and consequently bear a child, the child is then called also with “a syubhat child.” Nasab (bloodline or lineage) of a syubhat child, whether resulting from a watha 'syubhat or a syubhat marriage, is set to his father, or a person who has become his/ her watha', because a marriage whether it is shahih or fasid,  the nasab (lineage) of a child will remains to his/ her watha', not to his mother, because the Islamic law for a syubhat child is different from that of the illegitimate child. Keywords: Syubhat Marriage, Watha' Syubhat, Syubhat Child, Illegitimate Child. Abstrak: Allah sudah menetapkan semua perkara baik yang halal atau haram jelas dan diantara keduanya ada sesuatu yang disebut syubhat, dimana kebanyakan manusia terjerumus ke dalamnya dan mereka tidak tahu apakah itu halal atau haram. Apabila tidak tahu halal dan haram suatu hal, maka akan timbul suatu penyakit yaitu syubhat. Sebuah hubungan yang dilakukan karena ada sebuah unsur syubhat, baik yang terjadi pada sebuah pernikahan yang disebut syubhat dan kemudian difasakh,  atau terjadi pada watha’ yang disebut juga watha’ syubhat dan akibatnya melahirkan seorang anak, anak tersebut pun kemudian disebut pula dengan anak syubhat. Nasab anak syubhat baik yang dihasilkan dari watha’ yang syubhat atau pernikahan Syubhat  tetap kepada bapaknya, atau seorang yang telah mewatha’nya. Karena baik nikah shahih atau fasid nasab anak tetap kepada seorang yang mewatha’nya bukan kepada ibunya, karena anak syubhat hukumnya berbeda dengan anak zina. Kata kunci: Nikah syubhat, Watha’ syubhat, Anak syubhat, Anak zina